2021
DOI: 10.1002/fsn3.2456
|View full text |Cite
|
Sign up to set email alerts
|

Rapid and simultaneous determination of trigonelline, caffeine, and chlorogenic acid in green coffee bean extract

Abstract: Among the various agricultural outputs, coffee is one of the most popularly consumed beverage worldwide. Consequently, it has taken a significant market share in the World market and more than 121 countries are exporting coffee to different countries (http://www.ecea.org.et/uk/). Analysis of caffeine, trigonelline, and chlorogenic acid levels in green coffee is vital for the coffee industry because they have a paramount effect on the overall quality of the brewed coffee and coffee products (de Maria et al., 19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
5

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 37 publications
1
13
0
5
Order By: Relevance
“…Depending on the analyte, various extraction methods have already been developed. A simple solid–liquid infusion using hot water [ 11 , 34 , 47 , 59 , 88 , 139 , 140 , 141 , 142 , 143 ] or organic solvents [ 40 , 78 , 124 , 144 ] is the most common technique of PPs and caffeine isolation. Other extraction techniques, namely percolation [ 145 ], ultrasound-assisted [ 78 , 138 , 146 ] or microwave-assisted extractions [ 138 ], QuEChERS [ 78 ], and deep eutectic solvent-based extraction [ 95 ] have been used rarely.…”
Section: Analysis Of Antioxidants In Coffee Products Using Hplcmentioning
confidence: 99%
See 1 more Smart Citation
“…Depending on the analyte, various extraction methods have already been developed. A simple solid–liquid infusion using hot water [ 11 , 34 , 47 , 59 , 88 , 139 , 140 , 141 , 142 , 143 ] or organic solvents [ 40 , 78 , 124 , 144 ] is the most common technique of PPs and caffeine isolation. Other extraction techniques, namely percolation [ 145 ], ultrasound-assisted [ 78 , 138 , 146 ] or microwave-assisted extractions [ 138 ], QuEChERS [ 78 ], and deep eutectic solvent-based extraction [ 95 ] have been used rarely.…”
Section: Analysis Of Antioxidants In Coffee Products Using Hplcmentioning
confidence: 99%
“…However, their precise representation and quantity depend on many variables, such as the genotype of the coffee tree and its growing conditions (defined by the soil, climate, altitude, and other factors), post-harvest processing methods, the degree of the green coffee beans roasting, storage and distribution conditions, as well as coffee brewing methods [ 13 , 20 , 21 , 24 , 44 , 47 , 60 , 61 , 62 ]. Many studies have already been published in which elements [ 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 ], triglycerides [ 72 ], tocopherols [ 62 , 72 , 73 , 74 ], trigonellines [ 18 , 75 , 76 , 77 , 78 , 79 ], diterpenes [ 80 , 81 , 82 ], carbohydrates [ 76 , 83 , 84 , 85 , 86 , 87 ], polyphenols [ 36 , 37 , 39 , 65 , 75 , 76 , 77 , 78 , 88 , 89 , 90 , …”
Section: Introductionmentioning
confidence: 99%
“…The coffee compounds were identified by comparing HPLC retention times and spectral data (spectral shape and absorption maxima) with those of the corresponding standards. Herein, eight characteristic coffee compounds, namely, caffeine, caffeic acid, chlorogenic acid, cryptochlorogenic acid, neochlorogenic acid, nicotinic acid, theophylline, and trigonelline 2,8,[26][27][28]31) , were analyzed. The peak temperature was measured inside the roasting chamber.…”
Section: Hplc Analysismentioning
confidence: 99%
“…Coffee is a widely consumed beverage and contains many physiologically active compounds, including caffeine, trigonelline, and chlorogenic acid (5-O-caffeoylquinic acid) 1,2) . Numerous epidemiological studies have suggested that daily consumption of coffee may reduce the risk of several types of cancers, type-2 diabetes, and stroke 3−6) .…”
Section: Introductionmentioning
confidence: 99%
“…O ácido clorogênico, representado pelo ácido 5-cafeoilquínico, é o principal polifenol presente no café (TAJIK et al, 2017) ROSTAGNO et al, 2015;NAVARRA et al, 2017;SANTIAGO et al, 2020;ATLABACHEW et al, 2021).…”
Section: Avaliação Do Método De Extração E Diluiçãounclassified